A Narrative Review: Quintuple Helixs Model for Malaria Elimination in Indonesia - Yura Witsqa Firmansyah; Muhammad Fadli Ramadhansyah; Mirza Fathan Fuadi; Wahyu Widyantoro; Devin Ahnaf Rana Rizqullah; Ahlun Najaa Nazzun Priyono Putro; Siti Nurhidayati; Henny Lestyorini; Wahyu Istining Rahayu; Abdul Chodir; Gusman Arsyad; Rafika; Oryza Filial Zulkarnain; Tri Suwanti (Jurnal Kesehatan Mahardika, 2022)
Malaria continues to impact the health and economies of people around the world. Further steps need to be taken in accordance with the Global Technical Strategy for malaria to prevent malaria transmission. Quintuple helix model is an integrated effort that involves cross-sector in controlling malaria cases in an area. The implementation of the quintuple helix model is expected to be used as consideration and input for policy makers in an effort to achieve malaria elimination in Indonesia by 2030. The purpose of this study is to eliminate malaria in Indonesia with the quintuple helix model. This study uses a systematic review narrative method that is used to identify study topics selectively on interesting and recent issues. Malaria control in Indonesia is carried out using the national resilience approach. The results obtained from the academic aspect for malaria control must be met, both in terms of educational background qualifications, from the industrial aspect of the economic system included in the quintuple helix model, from the government aspect the control program must be compiled under the Ministry of Health, from the media aspect where the media is one of the an important index in the management of malaria in an area, and from an environmental aspect that aims to prevent, limit vector breeding and reduce mosquito contact with humans. The quintuple helix model is expected to be an innovation in malaria control in Indonesia. By involving academia and social community, industry, government, environmental engineering and the media. It is hoped that each sector can provide roles that are in accordance with their duties and functions